2012
DOI: 10.7314/apjcp.2012.13.4.1115
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Effect of Diallyl Sulfide on Colon Carcinogenesis in C57BL/6J-ApcMin/+Mice

Abstract: Diallyl sulfide (DAS), a flavoring compound derived from garlic, is considered to have cancer chemopreventive potential in experimental animals and humans. This study was designated to examine possible chemopreventive effects of DAS on colon carcinogenesis using genetically engineered transgenic Apc Min/+ mice, a well-established animal model for familial adenomatous polyposis (FAP) and sporadic colorectal cancer. Male C57BL/6J-Apc Min/+ mice were divided into three groups. Animals of group 1 were placed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…DAS has also been demonstrated to have anticancer properties against different cancers such as colon cancer, prostate cancer, skin cancer, etc. via modulation of inflammatory pathways [ 82 84 ].…”
Section: Active Components Of Spices Inflammatory Pathways and Chromentioning
confidence: 99%
“…DAS has also been demonstrated to have anticancer properties against different cancers such as colon cancer, prostate cancer, skin cancer, etc. via modulation of inflammatory pathways [ 82 84 ].…”
Section: Active Components Of Spices Inflammatory Pathways and Chromentioning
confidence: 99%
“…DAS treatment demonstrated a dose dependent inhibition towards expression of MMP-2 and −7 in colo 205 cells indicating its potential anti-metastatic properties. In animal model for familial adenomatous polyposis and sporadic colorectal cancer, DAS significantly reduced the incidence of colonic polyps in a dose-dependent manner [28]. Furthermore, results from a meta-analysis demonstrated a clinical association between high garlic intake and decreased risk for stomach and colorectal cancers [29].…”
Section: Das: Anticancer Effectsmentioning
confidence: 99%
“…A separate study testing the effects of dietary DAS supplementation in APC min mice found that supplementation with 100 to 300 ppm reduced the incidence of colonic polyps in a dose-dependent manner, although the inhibition was not statistically significant [ 109 ]. The authors claim that the lack of statistical significance is likely due to the relatively small number of mice used.…”
Section: Organosulfur Compounds Derived From Allium ...mentioning
confidence: 99%